Cloud Computing: “Secured Service Provider for data mining” (International Journal of Engineering and Computer Science, 2017)
Data safety and procedure in method are the most demanding scrutinize work going on, at present, in cloud computing. This is for the reason that of the clients sending their complex data to the cloud providers for obtaining their facilities. Thus, security concerns among users of the cloud have become a major barrier to the extensive growth of cloud computing. One of the security concerns of cloud is data mining based isolation attacks that involve analyzing data over a long period to extract valuable information. In particular, in current cloud architecture a client entrusts a single cloud provider with his data. It gives the provider and outside attackers having unlawful access to cloud, an occasion of analyze client data over a long period to take out sensitive information that causes privacy violation of clients. Therefore, to rise above these difficulties, a model (cloud architecture) is explained in this paper which accepts only those data which are essential in an encoded form, performs the service opted by the client and sends the result in the encoded format to be implicit by the specific client.